Medical students' perceptions on factors influencing a surgical career: the fate of general surgery in Greece. - Pikoulis, Emmanouil; Avgerinos, Efthimios D; Pedeli, Xanthi; Karavokyros, Ioannis; Bassios, Neofitos; Anagnostopoulou, Sofia (Surgery, 2010)
BACKGROUND: A decline of medical students' interest in a general surgery career is occurring in the Western medical world. We sought data on the mentality of Greek students toward specialty selection, and we determined whether trends indicated a decline in interest for general surgery in Greece. METHODS: A structured questionnaire was distributed to 3 groups of medical students: to pre-4th-year (group 1) surgical clerkship, post-4th-year (group 2) surgical clerkship, and post-6th-year internship students in surgery (group 3). The questions covered a wide spectrum of data including career choices, influential factors, and satisfaction rates on educational and training issues. RESULTS: From a total of 500 distributed questionnaires 363 were returned. Most students (63.1%) indicated preference toward nonsurgical (medical) specialties. Surgical specialties within the 3 groups gathered 19.5% (group 1), 26.5% (group 2) and 31.2% (group 3) preference rates. Among surgical specialties, general surgery was chosen by 29.4% in group 1, 10.0% in group 2, and 17.9% in group 3. The most common criterion for specialty selection was "quality of life" (68.6%) among group 1 students and "patient contact" for group 2 and group 3 students (77.3% and 65.3%, respectively). Among the 96 students who chose surgical specialties, the most common criterion for specialty selection was "scientific challenge" (100%) in group 1 and "patient contact" in groups 2 and 3 (62.5% and 69.2%, respectively). The 3 more frequently chosen factors that influenced the "picture" of surgery positively were attending live surgery cases in the operating room (37.6%), clinical experience (29.6%), and patient care (14.4%), followed by assisting in the operating room (8.8%). CONCLUSION: Our survey suggests a limited interest of Greek medical students for surgical specialties and general surgery in particular. As the medical curriculum is restructured, our data underscore the need for actions by surgical educators and medical school authorities so as to enhance the interest of medical students in general surgery in Greece.
Keywords: Career Choice; Choice Behavior; General Surgery; Greece; Humans; job satisfaction; Medicine; Perception; Physician-Patient Relations; Quality of Life; Specialties, Surgical; Students, Medical; Surveys and Questionnaires; Waiting Lists